Monotone contracts. Issue 3 (28th July 2022) - Bird, Daniel; Frug, Alexander
Abstract : We develop a framework for deriving dynamic monotonicity results in long‐term stochastic contracting problems with symmetric information. Specifically, we construct a notion of concave separable activity that encompasses many prevalent contractual components (e.g., wage, effort, level of production, etc.). We then provide a tight condition under which such activities manifest a form of seniority in every contracting problem in which they are present: any change that occurs in the level of the activity over time favors the agent. Our work unifies and significantly generalizes many existing results and can also be used to establish monotonicity results in other settings of interest.